2018
DOI: 10.1371/journal.pone.0192773
|View full text |Cite|
|
Sign up to set email alerts
|

A quick aphasia battery for efficient, reliable, and multidimensional assessment of language function

Abstract: This paper describes a quick aphasia battery (QAB) that aims to provide a reliable and multidimensional assessment of language function in about a quarter of an hour, bridging the gap between comprehensive batteries that are time-consuming to administer, and rapid screening instruments that provide limited detail regarding individual profiles of deficits. The QAB is made up of eight subtests, each comprising sets of items that probe different language domains, vary in difficulty, and are scored with a graded s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 46 publications
3
105
1
3
Order By: Relevance
“…In the first session, the study was explained to them and they provided written informed consent, demographic and medical history information, and were screened for MRI safety. To characterize language deficits, they completed one of three equivalent forms of Quick Aphasia Battery (QAB; Wilson, Eriksson, Schneck, & Lucanie, ), as well as the Western Aphasia Battery (WAB; Kertesz, ). Because the adaptive semantic matching task depends on comprehension and semantic processing of written words, patients then completed the written word to picture matching subtest of the Comprehensive Aphasia Test (Swinburn et al, ), written word to picture matching using the word comprehension items from another form of the QAB, and a 14‐item short version (Breining et al, ) of the Pyramids and Palm Trees Test (Howard & Patterson, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the first session, the study was explained to them and they provided written informed consent, demographic and medical history information, and were screened for MRI safety. To characterize language deficits, they completed one of three equivalent forms of Quick Aphasia Battery (QAB; Wilson, Eriksson, Schneck, & Lucanie, ), as well as the Western Aphasia Battery (WAB; Kertesz, ). Because the adaptive semantic matching task depends on comprehension and semantic processing of written words, patients then completed the written word to picture matching subtest of the Comprehensive Aphasia Test (Swinburn et al, ), written word to picture matching using the word comprehension items from another form of the QAB, and a 14‐item short version (Breining et al, ) of the Pyramids and Palm Trees Test (Howard & Patterson, ).…”
Section: Methodsmentioning
confidence: 99%
“…The patients spanned a range of aphasia severity: per WAB criteria, five had severe aphasia, four had moderate aphasia, six had mild aphasia, and one was within normal limits. The patients’ language function is described in more detail elsewhere (Wilson et al, ). Written word comprehension was excellent in all but one of the patients, the only exception being the person with the most severe Broca's aphasia, who comprehended about two thirds of written words.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 1970s it was discovered that Broca's aphasia is also associated with particular sentence comprehension deficits that suggested a fundamental syntactic problem (Caramazza & Zurif, 1976), kicking off decades of intense investigation of the role of Broca's area in syntactic processing, assessed primarily via comprehension tasks (Grodizinsky & Amunts, 2006;Matchin & Rogalsky, 2017). However, while some large-scale lesion-deficit mapping studies have reported an association between damage to Broca's area and comprehension of syntactically complex and/or non-canonical sentence structures (Wilson et al, 2011;Magnusdottir et al, 2013;Mesulam et al, 2015;Fridriksson et al, 2018), many others have primarily implicated the posterior temporal lobe in basic syntactic processing and not Broca's area (Dronkers et al, 2004;Wilson & Saygin, 2004;Baldo & Dronkers, 2007;Peelle et al, 2008;Pillay et al, 2017;Rogalsky, et al 2018;Wilson et al, 2018b;2018c).…”
Section: Introductionmentioning
confidence: 99%